Blocking Extracellular Chaperones to Improve Cardiac Regeneration - Seclì, Laura; Sorge, Matteo; Morotti, Alessandro; Brancaccio, Mara (Frontiers in Bioengineering and Biotechnology, 2020)
Chronic or acute insults to the myocardium are responsible for the onset of cardiomyopathy and heart failure. Due to the poor regenerative ability of the human adult heart, the survival of cardiomyocytes is a prerequisite to support heart function. Chaperone proteins, by regulating sarcomeric protein folding, function, and turnover in the challenging environment of the beating heart, play a fundamental role in myocardial physiology. Nevertheless, a number of evidences indicate that, under stress conditions or during cell damage, myocardial cells release chaperone proteins that, from the extracellular milieu, play a detrimental function, by perpetuating inflammation and inducing cardiomyocyte apoptosis. Blocking the activity of extracellular chaperones has been proven to have beneficial effects on heart function in preclinical models of myocardial infarction and cardiomyopathy. The application of this approach in combination with tissue engineering strategies may represent a future innovation in cardiac regenerative medicine.